Transcriptional Responses of Paxillus involutus and Betula pendula During Formation of Ectomycorrhizal Root Tissue - Tomas Johansson; Antoine Le Quéré; Dag Ahren; Bengt Söderström; Rikard Erlandsson; Joakim Lundeberg; Mathias Uhlén; Anders Tunlid (Molecular Plant-Microbe Interactions, 2004)
In order to obtain information on genes specifically expressed in the ectomycorrhizal symbiosis, 3,555 expressed sequence tags (ESTs) were analyzed from a cDNA library constructed from ectomycorrhiza formed between the basidiomycete Paxillus involutus and birch (Betula pendula). cDNA libraries from saprophytically growing fungus (3,964 ESTs) and from axenic plants (2,532 ESTs) were analyzed in parallel. By clustering all the EST obtained, a nonredundant set of 2,284 unique transcripts of either fungal or plant origin were identified. The expression pattern of these genes was analyzed using cDNA microarrays. The analyses showed that the plant and fungus responded to the symbiosis by altering the expression levels of a number of enzymes involved in carbon metabolism. Several plant transcripts with sequence similarities to genes encoding enzymes in the tricarboxylic cycle and electron transport chain were down regulated as compared with the levels in free-living roots. In the fungal partner, a number of genes encoding enzymes in the lipid and secondary metabolism were down regulated in mycorrhiza as compared with the saprophytically growing mycelium. A substantial number of the ESTs analyzed displayed significant sequence similarities to proteins involved in biotic stress responses, but only a few of them showed differential expression in the mycorrhizal tissue, including plant and fungal metal-lothioneins and a plant defensin homologue. Several of the genes that were differentially expressed in the mycorrhizal root tissue displayed sequence similarity to genes that are known to regulate growth and development of plant roots and fungal hyphae, including transcription factors and Rho-like GTPases.